Groundwater quality mapping for drinking and irrigation purposes using statistical, hydrochemical facies, and water quality indices in Tercha District, Dawuro Zone, Southern Ethiopia - Arefegn Arota; Abunu Atlabachew; Abel Abebe; Muralitharan Jothimani (Brawijaya University, 2022)
When groundwater quality is good, it may be a substantial water supply for various applications. However, no systematic research on hydrogeochemistry and water quality features for drinking and irrigation has been undertaken in the present study area. As a result, the current study looked at hydrogeochemical variables and groundwater quality for drinking and irrigation in Tercha district, Dawuro Zone, Southern Ethiopia. Forty-seven groundwater samples were collected and tested to satisfy the required target for various physicochemical properties. The hydrogeochemical features of the groundwater in the study region were assessed using in-situ testing and laboratory analysis of physicochemical parameters. Groundwater samples from the research region were slightly acidic to slightly basic, with the principal cations and anions decreasing in sequence: Na+ > Ca2+ > Mg2+ > K+ and HCO3-> Cl-> SO42-. The hadrochemical facies of the studied region evolved from mildly mineralized dominant highland Ca-HCO3 water types to moderately mineralized mixed Ca-Na-HCO3 water types to highly mineralized deep rift floor Na-HCO3 water types. Additionally, the World Health Organization and the Ethiopian Standard Agency were utilized to compare the drinking water quality. Except for NO3- (4.25 %), Fe (8.51 %), and F- (2.12%), all groundwater samples from the research region were determined to be within permitted limits and appropriate for drinking. According to the Water Quality Index, about 80.86% of groundwater samples are excellent, and 19.14% are good drinking water. Sodium absorption ratio (SAR), sodium (Na) percentage, residual sodium carbonate RSC, permeability index (PI), and magnesium hazard were among the irrigation water quality indicators calculated (MH). The great majority of groundwater samples are suitable for agricultural use.